Analysis of the CFO Successive Interference Cancellation for the OFDMA Uplink - González, Gustavo J. (2016)
The uplink of orthogonal frequency division multiple access or single-carrier frequency division multiple access suffers multiple access interference when carrier frequency offset (CFO) is not properly estimated and compensated. In particular, multicarrier uplink CFO compensation is highly complex due to the multiuser context. Successive interference cancellation algorithms are effectively employed to compensate for the CFO, where the interference produced by each user is handled sequentially through a series of iterations. The main contribution of this work is the analysis of the CFO compensation performance of efficient successive cancellation algorithms. We study the mean square symbol error, and derive a useful upper-bound of the compensation technique performance at convergence. This result extends the general convergence results for the space-alternating generalized expectation-maximization algorithm in the CFO compensation scenario. Finally, we validate the analysis with numerical simulations.